Physico-chemical aspects of Chandbill Oxbow lake of Meherpur, Bangladesh - Kabir, AKM Nazrul; Naser, M Niamul (Dhaka University Journal of Biological Sciences, 2011)
Some physico-chemical parameters of Chandbill Baor, a natural oxbow lake of Meherpur district were studied from September 2006 to August 2007. Air temperature of the study area varied from 18.10 to 32.10°C (x-bar± SE : 27.73 ± 1.22°C). The Water temperature (17.10 to 32.10°C; x-bar± SE: 28.24 ± 1.32°C), Secchi disc depth (8.89 to 53.34 cm; x-bar± SE : 26.19 ± 4.29 cm), water depth (132.08 to 307.34 cm; x-bar± SE : 183.93 ± 13.88 cm); total alkalinity (51.3 to 85.5 mg/l; x-bar± SE : 68.4 ± 3.64 mg/l), total hardness (85.5 to 188.10 mg/l; x-bar± SE : 125.81 ± 9.38 mg/l), dissolved oxygen (5.0 to 12.0 mg/l; x-bar± SE: 8.42 ± 0.62 mg/l), free CO2 (5.0 to 30.0 mg/l; x-bar± SE : 14.58 ± 2.64 mg/l), pH (8.0 to 10; x-bar± SE : 8.54 ± 0.19), ammonia-nitrogen (0.3 to 0.7 mg/l; x-bar± SE: 0.46 ± 0.04 mg/l) in the 'Baor' water were found to be suitable for survival of aquatic fauna. Nitrite-nitrogen was absent in the 'em>Baor' throughout the year. Positive correlations were observed in between air and water temperature (r = 0.978); free CO2 and Secchi depth (r = 0.839), free CO2 and water depth (r = 0.714); water depth and Secchi depth (r = 0.903); total hardness and total alkalinity (r = 0.861) and pH with DO (r = 0.661). However, inverse relations were observed among ammonia-nitrogen with water depth (r = −0.727); ammonia-nitrogen with Secchi disc depth (r = −0.840); dissolved oxygen with free CO2 (r = −0.636); pH with Secchi disc depth (r = −0.581) and pH with free CO2 (r = −0.825). The productivity of the lake was found to be medium and could be improved to higher level. Alkaline pH (8.54 ± 0.19) was supposed to be helpful for proper growth and development of fishes and aquatic organisms. This is the first limnological report from a natural ‘Baor’ (Oxbow lake) of Meherpur district, Bangladesh. Key words: Physico-chemical aspects; Oxbow lake; Meherpur DOI: http://dx.doi.org/10.3329/dujbs.v20i1.8835 Dhaka Univ. J. Biol. Sci. 20(1): 31-39, 2011 (January)